Urgensi Asas Itikad Baik dalam Penyelesaian Perkara Hak Cipta melalui Prosedur Penyelesaian Sengketa Di Luar Pengadilan - Ni Putu Riyani Kartika Sari (Fakultas Hukum Universitas Ngurah Rai, 2019)
Intellectual Property Rights is an intangible object that has economic value so that it can be utilized by its creator to support their life. This may causes some Copyright dispute because some parties who unlawfully commit acts that are detrimental to the creator. As regulated in the Copyright Law that Copyright Cases consist of criminal, civil and administrative cases, which can be settled through Arbitration, Alternative Dispute Resolution and Courts. If referring to the provisions in the Law of Arbitration and Alternative Dispute Resolution, the settlement through Alternative Dispute Resolution shall be carried out by the Parties in good faith. Therefore in this paper aims to examine the urgency of the good faith principle in the settlement of copyright cases through the resolution of disputes outside the court (Alternative Dispute Resolution). We can explain that the principle of good faith is a universal principle, where good faith means both honesty and objectively means propriety. This results in Alternative Dispute Settlement that is conducted outside the judicial process is important to be based on the principle of good faith because, the dispute resolution occurs and is carried out purely by the parties to the dispute. So that the principle of good faith becomes the basis for dispute resolution that can fortify the parties to negotiate, agree, and implement agreements to comply with applicable norms so as to produce decisions that resolve cases, not cause harm to either party, and do not create new problems later on.